Competition among liquidity providers with access to high-frequency trading technology - Bongaerts, Dion; Achter, Mark Van (Journal of Financial Economics, 2021)
We model endogenous technology adoption and competition among liquidity providers with access to High-Frequency Trading (HFT) technology. HFT technology provides speed and information advantages. Information advantages may restore excessively toxic markets. Speed advantages may reduce resource costs for liquidity provision. Both effects increase liquidity and welfare. However, informationally advantaged HFTs may impose a winner’s curse on traditional market makers, who in response reduce their participation. This increases resource costs and lowers the execution likelihood for market orders, thereby reducing liquidity and welfare. This result also holds when HFT technology dominates traditional technology in terms of costs and informational advantages.